2016
DOI: 10.1111/epi.13441
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of health‐related quality of life in children with drug resistant epilepsy

Abstract: SUMMARYObjective: Health-related quality of life (HRQL) is compromised in children with epilepsy. The current study aimed to identify correlates of HRQL in children with drug resistant epilepsy. Methods: Data came from 115 children enrolled in the Impact of Pediatric Epilepsy Surgery on Health-Related Quality of Life Study (PEPSQOL), a multicenter prospective cohort study. Individual, clinical, and family factors were evaluated. HRQL was measured using the Quality of Life in Childhood Epilepsy Questionnaire (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 52 publications
4
43
1
Order By: Relevance
“…Caregiver anxiety and caregiver satisfaction with family relationships contributed most strongly to child QOL over time. This finding is consistent with previous research highlighting the dominant effects of psychosocial factors, such as parental psychopathology and the family environment more broadly, on child QOL at baseline and longitudinally, relative to clinical factors. One exception is AED side effects, a seizure‐related variable that was not captured in the current study but that has been identified as a consistent predictor of QOL in children with epilepsy …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Caregiver anxiety and caregiver satisfaction with family relationships contributed most strongly to child QOL over time. This finding is consistent with previous research highlighting the dominant effects of psychosocial factors, such as parental psychopathology and the family environment more broadly, on child QOL at baseline and longitudinally, relative to clinical factors. One exception is AED side effects, a seizure‐related variable that was not captured in the current study but that has been identified as a consistent predictor of QOL in children with epilepsy …”
Section: Discussionsupporting
confidence: 92%
“…Data were collected as part of the Impact of Pediatric Epilepsy Surgery on Health‐Related Quality of Life Study (PEPSQOL), a multicenter longitudinal prospective cohort study . Participants were recruited between April 2014 and September 2016 while being evaluated for epilepsy surgery at eight centers across Canada.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research supporting the importance of knowledge in this area comes from studies demonstrating that caregiver burden is significantly associated with the child with epilepsy's quality of life [21,24,32]. For example, in one study, the level of a mother's caregiver stress was found to be moderately to strongly associated with behavior problems in the child [21].…”
Section: Identify the Factors That Influence Ds Caregiving Burden As mentioning
confidence: 99%